130k views
25 votes
X-2y=1;3x-6y=3 substitution

User Neelesh
by
5.1k points

1 Answer

5 votes

Answer:

All solutions

Explanation:

When solving by substitution, we will first set one equation equal to a variable, and then plug that value into the second equation as the variable. Here is what I mean;

x - 2y = 1

3x - 6y = 3

-

x = 1 + 2y

3x - 6y = 3

-

3(1 + 2y) - 6y = 3

3 + 6y - 6y = 3

3 = 3

[] Oh no! This doesn't work well. Let's graph it and see what is happening;

-> See attached

-> I have made the lines very thick so you can see the overlap, they are the same size in reality

The answer is all solutions because the graphs are exactly the same.

Have a nice day!

I hope this is what you are looking for, but if not - comment! I will edit and update my answer accordingly.

- Heather

X-2y=1;3x-6y=3 substitution-example-1
User Zaczap
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.